Time-spatial analysis of the effect of the implementation of weighing stations on the esals for pavement design - Ureña Bermúdez, Allan Gerardo (2025)
The truck factor is one of the main components in computing the load demand for highway pavements. The aim of this study is to analyse the databases on weighing carried out between 2008 and 2017. Therefore, more than 12 million heavy transport vehicles were counted, these vehicles were distributed in Limon and Cartago weighing stations. For each vehicle, the associated truck factor was calculated. Besides, according to the weight of each of its axles, it was determined if the vehicle did not comply with the provisions of the Legal Decree no 31363 of the MOPT. The econometric models are computed from the truck factor variables and non-compliance percentages. These models take the effect from different variables of the type of truck on the truck factor and non-compliance: spatial and temporal, and the type of measurement. The econometric models consider the following variables: year, month, type of vehicle, day, hour, and the type of measurement applied in the analysed stations. One of the results of this research is that there was an increase in the truck factors and non-compliance percentages analysed when going from a manual weighing system to an automated one.